"Responding to the thing that it is": a study of new play development in English theatres. Issue 1 (2nd January 2019) - Tyler, Lucy
Abstract: This paper outlines a study of play development practices in key state-subsidised English theatres in 2014 and 2015. Literary managers, dramaturgs and directors were interviewed about their approach to play development in the nine theatres in which they worked: West Yorkshire Playhouse, Plymouth Drum, The Birmingham Repertory Theatre, The Mercury Theatre, The Liverpool Everyman, The Manchester Royal Exchange, The Royal Shakespeare Company, The Royal Court Theatre and The National Theatre. This paper outlines the context of this study, including an examination of existing theoretical and empirical research on contemporary, English play development. It outlines the methodology used for the data collection, presents the interview responses and concludes with a short summary of some key findings.